137k views
1 vote
Multiply (6x-6)(x+6)

2 Answers

4 votes

FOIL method : F = First , O = Outer , I = Inner, L = Last

(6x-6)(x+6)

First: 6x * x = 6x^2

Outer: 6x * 6 = 36x

Inner: -6 * x = -6x

Last: -6 *6 = -36

Put these in order and we get : 6x^2 + 36x -6x -36

User Yvan
by
4.9k points
5 votes

Hey there!


(6x + (-6)) (x +6) \\ \\ 6x(x) + 6x(6) + (-6) (x) + -6 (6) \\ \\ 6x(x) = 6x^2 \\ \\ 6x(6) = 36x \\ \\ -6(6) = -36 \\ \\ 6x^2 + 36x - 6x -36 \\ \\ 36x - 6x = 30x \\ \\ Answer: 6x^2 + 30x -36

Good luck on your assignment and enjoy your day!

~
LoveYourselfFirst:)

User Davor Zubak
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.